(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The aim of the article is to discuss the methods and criteria for the distribution of funds allocated to support regional development. Evolutionary changes in the allocation of funds at national and EU level were examined in the in the analyzes. Also the following aspects were described: distribution criteria and their impact on the size of the funds raised at the national and regional disposal. The study included pre-accession period and the financial perspectives for 2007-2013 and 2014-2010. The funds obtained significantly contributed to the achievement of the objectives set in the regional development strategies.